First national survival data for colorectal cancer among Saudis between 1994 and 2004: what’s next? - Al-Ahwal Mahmoud S; Shafik Yasmin H; Al-Ahwal Hazem M (BMC Public Health, 2013)
Abstract Background Colorectal cancer (CRC) is the second most common malignancy in the Saudi population. This study aimed to review CRC data from the Saudi Cancer Registry (SCR) in order to evaluate the prognostic factors for CRC survival in Saudi patients. Methods This study was a retrospective censored overall survival (OS) analysis of CRC data for the period 1994–2004 obtained from the SCR. Data were collected from all 13 administrative regions of the Kingdom of Saudi Arabia (KSA) by the SCR in collaboration with the National Information Center of the Ministry of Interior. The Kaplan-Meier method was used to calculate the cumulative survival rate, which was then stratified by gender and by period (1994–1999 versus 2000–2004). The clinico-pathological variables that might affect CRC survival were analyzed by Cox regression analysis. Results Between 1994 and 2004, 549 CRC cases were diagnosed (363 [66.1%] in males and 186 [33.9%] in females). The OS for CRC during this period was 44.6% (44.7% for 1994–1999 and 44.3% for 2000–2004 [p=0.7]). There was a significant (p=0.003) discrepancy of 9.6% between the male five-year OS (41.0%) and the female five-year OS (50.6%). The five-year OS was 63.3% for patients with localized disease, 50.2% for those with regional disease, and 14.7% for patients with metastases. By Cox regression analysis, age and extent were significant prognostic factors of survival in patients with colon cancer; the risk was higher in patients with distant metastasis (hazard ratio [HR], 2.53; 95% confidence interval [CI], 1.17-5.45; p=0.01). In patients with rectal cancer, the risk was lower in males (HR, 0.66; CI, 0.45-0.98; p=0.04), but higher in patients with unknown tumor extent (HR, 3.70; 95% CI, 1.66-8.24; p=0.01). Conclusions The five-year OS for 1994–2004 was 44.6% for patients with CRC. More so, five-year OS based on CRC stage was generally lower than the typically reported survival rates. The establishment of a national screening program and increased access to specialized medical faculties may be necessary to improve CRC survival in the KSA.